Evaluation of The Inhibitory Effectiveness of Aqueous Onion and Garlic Extract Against the Growth of Certain Pathogenic Bacteria - Faid, Kholod Alhadi; Ali, Hasan Mohamed; Gwailah, Keri; Kondi, Boshra Mohamed (The annual Scientific Conference for Under and Postgraduate Students at the University., 2023)
These days, treatment with plant extracts occupies a large space in the treatment of diseases. Examples of this include onion and garlic plants, which have an effective effect in combating and eliminating bacteria. This is the goal of the research. The current study aims to study the inhibitory effect of aqueous onion and garlic extract on the growth of some types of pathogenic bacteria, and compare it with antibiotics. Five types of pathogenic bacteria that were obtained and diagnosed at Zliten Medical Center were used in this study. The results showed that fresh aqueous garlic extract has a strong effect on bacteria, and the areas are free of any bacterial components. It can be used as an alternative to antibiotics, unlike onion extract, where the bacterial species were not affected by it. In general, fresh extracts have an effect on bacteria, unlike imported dry plant extracts that It did not give any effect on bacteria. In addition, the effectiveness of fresh plant extracts increases directly with increasing concentration. The higher the concentration of the extract, the greater its effectiveness in eliminating the bacterial environment.